Hubungan Antara Kualitas Pelayanan Dengan Kepuasan Konsumen Pada Mahasiswa Pengguna Game Pointblank - Harun, Haerul Isra (EMPATHY Jurnal Fakultas Psikologi, 2013)
AbstractThis study aimed to determine the relationship between service quality and satisfaction of the consumer at point blank student game users. The participants filled two scales are scales of service quality and customer satisfaction. The results showed there was a significant positive relationship between service quality to customer satisfaction. Indicated by the correlation coefficient rxy = 0.463 with a significance level of 0.000 (p <0.01). The effective contribution of 21.5%Keywords: quality of service and customer satisfactionÂ